Merchants and mariners : selected maritime writings of David M. Williams - Scholl, Lars Ulrich; Williams, David M. (David Malcolm), 1940- (Research in maritime history, 2000)
This book presents twelve essays by historian David M. Williams, in order to pay tribute to his career. The essays stretch from 1807 through to the end of the nineteenth century, and address both economic and social themes. Topics include maritime trade, deployment of merchant ships, the state regulations concerning shipping, shipwrecks and loss of life, passenger cargoes, slavery, cotton, timber and coffee trades, and the working conditions of seamen over the course of the century. The plight of the maritime labourer is at the core of this collection. The essays primarily focus on British shipping, and firmly places it within an international context. The book is introduced by Lars U. Scholl, followed by two tributes to Williams' career, one by Peter N. Davies, the other by Lewis R. Fischer. Scholl concludes the volume with a thorough bibliography of Williams' maritime writings: books, chapters, and articles.